Fruit quality retention and shelf-life extension of papaya through organic coating - Sazia Jahan; Joydeb Gomasta; Jahidul Hassan; Md Habibur Rahman; Md Abdul Kader; Emrul Kayesh (Heliyon)
Papaya (Carica papaya L.) is a climacteric fruit which lose quality and shelf life quickly due to physiological decay and microbial infection after harvest. The study was conducted to evaluate newly applied clybio formulation (0.2 %) along with the existing effective concentration of chitosan (1 %), aloevera gel (50 %), seaweed extract (1 %) and uncoated papaya (control) fruits on post-harvest physicochemical properties and disease incidence when stored at 25 ± 1 °C and 85–90 % relative humidity. Quality parameters were available up to 12 days of storage (DAS) for chitosan and clybio treated papaya where it was 9 DAS for aloevera gel and seaweed treated papaya and 6 DAS for control papaya. Before decay of all the coated papaya at 9 DAS, chitosan (1 %) performed superior in retaining maximum reducing sugar (0.77 %, 1.41 % and 3.85 % more than aloevera, seaweed and clybio application, respectively), β-carotene (10.94 %, 12.5 % and 9.89 % greater than aloevera, seaweed and clybio coatings, respectively), total flavonoids content (18.36 %, 29.81 % and 25.29 % better than aloevera, seaweed and clybio treatments, respectively), total antioxidant activity (21.85 %, 68.2 % and 47.91 % than noted in aloevera, seaweed and clybio formulations, respectively) and potassium content (3.14 % and 9.32 % than aloevera and clybio treatments, respectively). In addition, clybio gave better results over chitosan up to completion of shelf life (12 DAS) such as retention of ascorbic acid (6.21 %), non-reducing sugar (13.48 %), magnesium content (8.31 %) and disease incidence (20 %). Thus, besides preserving nutraceutical property, chitosan and clybio coated papaya remained edible for further 6 days compared to control, and 3 days over aloevera gel and seaweed extract treatment. These findings suggest the use of chitosan and clybio formulation for preserving quality parameters and extending the storage life of papaya.